Nitrogen isotope fractionation explains the 15N enrichment of Antarctic cryptogams by volatilized ammonia from penguin and seal colonies - Bokhorst, Stef; van Logtestijn, Richard; Convey, Peter; Aerts, Rien (Polar Research, 2019)
Vegetation near bird and seal rookeries typically has high δ15N signatures and these high values are linked to the enriched δ15N values of rookery soils. However, Antarctic cryptogams are mostly dependent on atmospheric ammonia (NH3) and volatized NH3 from rookeries is severely depleted in δ15N-NH3. So there is an apparent discrepancy between the isotopically depleted source (NH3) and δ15N-enriched vegetation. In this article, we aim to resolve this discrepancy to better understand the mechanisms and processes involved in isotopic changes during nitrogen transfer between Antarctic marine and terrestrial ecosystems. Under laboratory conditions, we quantified whether volatized NH3 affects the isotopic signature of cryptogams. NH3 volatilizing from penguin guano and elephant seal dung was depleted (44–49‰) in δ15N when captured on acidified filters, compared to the source itself. Cryptogams exposed to the volatized NH3 were enriched (18.8–23.9‰) in δ15N. The moss Andreaea regularis gained more nitrogen (0.9%) than the lichen Usnea antarctica (0.4%) from volatilized NH3, indicating a potential difference in atmospheric NH3 acquisition that is consistent with existing field differences in nitrogen concentrations and δ15N between mosses and lichens in general. This study clarifies the δ15N enrichment of cryptogams resulting from one of the most important nitrogen pathways for Antarctic vegetation.
Keywords: Antarktis; fugler; kjemiske analyser; kryptogamer; lav; moser; planter; seler; økologi

Psoroma antarcticum, a new lichen species from Antarctica and neighbouring areas - Park, Chae Haeng; Hong, Soon Gyu; Elvebakk, Arve (Polar Biology, 2018)
Keywords: Antarktis; biodiversitet; botanikk; lav; moser; planter

Description of plant communities on Half Moon Island, Antarctica - Schmitz, Daniela; Putzke, Jair; Pereira de Albuquerque, Margéli; Schünemann, Adriano Luis; Costa Beber Vieira, Frederico; de Carvalho Victoria, Filipe de Carvalho Victoria; Batista Pereira, Antônio (Polar Research, 2018)
During February–March of the austral summers of 2013/14 and 2014/2015, fieldwork was performed on Half Moon Island, South Shetland Archipelago, Antarctica, to evaluate the distribution and abundance of mosses and lichens, as well as to describe and map the plant communities there. The quadrat (20 × 20 cm) sampling method was employed in a phytosociological study that aimed to describe these communities. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The number of species totalled 38 bryophytes, 59 lichens, only one flowering plant (Deschampsia antarctica Desv.), and two macroscopic terrestrial algae. Five types of plant communities were identified on the island, as follows: (1) fruticose lichen and moss cushion, (2) moss carpet, (3) muscicolous lichen, (4) crustose lichen and (5) moss turf.
Keywords: Antarktis; botanikk; bryozoa; flora; fytososiologi; lav; moser; planter; økologi

Patterns of fungal–algal symbiont association in Usnea aurantiaco-atra reveal the succession of lichen–moss communities in Fildes Peninsula, Antarctica - Cao, Shunan; Peng, Fang; Zheng, Hongyuan; Liu, Chuanpeng; Zhou, Qiming (Polar Research, 2017)
Usnea aurantiaco-atra is the most widespread flora in Fildes Peninsula. There are two growth types of U. aurantiaco-atra: the erect form on rocks and the prostrate form associated with mosses. Phylogenetic analysis showed that individuals of the two growth forms share genotypes. Moreover, haploid disequilibrium testing indicated no significant genetic difference for the two growth forms when fungal and algal internal transcribed spacer rDNA were treated as two alleles of one lichen individual. The two growth forms of U. aurantiaco-atra appear to reflect different stages of lichen–moss community succession. A mode is proposed for demonstrating the occurrence of this succession.
Keywords: Antarktis; botanikk; flora; fylogenetikk; lav; moser; planter

Characterization and mapping of plant communities at Hennequin Point, King George Island, Antarctica - Victoria, Filipe de C; de Albuquerque, Margéli P; Pereira, Antonio B; Simas, Felipe N B; Spielmann, Adriano A; Schaefer, Carlos E G R (Polar Research, 2013)
King George Island is the largest island and the principal area used for research bases in Antarctica. Argentina, Brazil, Chile, China, Poland, Russia, South Korea and Uruguay have permanent open bases on this island. Other countries have seasonal summer stations on different parts of this island, which demonstrates that human impact is strong on King George Island relative to other areas in the maritime and continental Antarctica. The objective of this work was to present a phytosociological approach for ice-free areas of Hennequin Point, eastern coast of Admiralty Bay, King George Island. The study started with the classification and description of the plant communities based primarily on phytosociological and biodiversity data. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The plant communities were described as follows: (1) lichen and moss cushion formation; (2) moss carpet formation; (3) fellfield formation; (4) grass and cushion chamaephyte formation; and (5) Deschampsia Antarctica–lichen formation. Characterizations and distributions of the plant communities are presented on a map at a scale of 1:5000. The plant communities found at Hennequin Point, in general, differ from those found in other areas of the Admiralty Bay region, probably because of the concentration of skua nests in the area and the relief singularities. We conclude by highlighting the importance of the study of plant species found in the ice-free areas of the Antarctic with respect to environmental monitoring and for evaluating global climate and environmental changes. Keywords: Plant communities mapping; lichens; mosses; flowering plants; Antarctic
Keywords: Antarktis; biodiversitet; fytososiologi; klimaendringer; lav; miljøendringer; moser; planter; plantesosiologi

Photosynthetic responses of selected Antarctic plants to solar radiation in the southern maritime Antarctic - Montiel, Pedro; Smith, Andrew; Keiller, Don (Polar Research, 1999)
The effects of UV-B exclusion and enhancement of solar radiation on photosynthesis of the two phanerogams which occur in the maritime Antarctic, Deschampsia antarctica and Colobanthus quitensis, and the moss Sanionia uncinats were investigated. Data on air temperature and solar radiation illustrate a drastic seasonal variation. Daily O3 column mean values and UV-B measured at ground level document the occurrence of the O3“hole” in the spring of 1997, with a concomitant increase in UV-B. The grass, D. antarctica, exhibited a broad temperature optimum for photosynthesis between 10–25°C while photosynthesis did not saturate even at high irradiance. The high water use efficiencies measured in the grass may be one of the features explaining the presence of this species in the maritime Antarctic. The net photosynthesis response to intercellular CO2 (A/ci) for D. antarctica was typical of a C3 plant. Exposure to a biologically effective UV-B irradiance of 0.74 W M-2 did not result in any significant change in either the maximum rate of photosynthesis at saturating CO2 and light, or in the initial carboxylation efficiency of Rubisco. (Vc,max). Furthermore while ambient (or enhanced) solar UV-B did not affect photochemical yield, measured in the field, of C. quitensis and D. antarctica, UV-B enhancement did affect negatively photochemical yield in S. uncinata. In D. antarctica plants, exposure to UV-B at low irradiances elicited increased flavonoid synthesis. The observed effects of UV-B enhancement on the moss (decreased photochemical yield) and the grass (increase in flavonoids) require further, separate investigation.
Keywords: Antarktis; botanikk; fotosyntese; klimaendringer; moser; planter

Responses of terrestrial plants and invertebrates to environmental change at high latitudes - Callaghan, Terry V.; Sonesson, Mats; Sømme, Lauritz; Walton, D. W. H.; Christensen, T.; Block, W. C.; Drewry, D. J.; Laws, Richard Maitland; Pyle, John Adrian (Philosophical Transactions of the Royal Society of London. Series B: Biological Sciences, 1997)
Many invertebrates show flexibility in their life cycles and are likely to respond to changes in climate as they have in the past. However, changes in temperature and photoperiod may disturb the life cycles of some existing polar invertebrates while continuing to constrain the polewards migration of more temperate species. Higher plants are likely to have higher productivity as temperatures and atmospheric CO2 levels increase but this productivity will be reduced by exposure to increasing UV-B radiation. Higher plants migrate more slowly than the rate at which climate is predicted to change and many species will be trapped in supra-optimal climates. Both mosses and lichens can migrate faster than higher plants, propagules of non-polar species already reaching the Antarctic, but they have fewer mechanisms of responding to changing environments. Polar vegetation and ecosystems provide feedback to the climate system: positive feedbacks are associated with decreases in reflectivity and increased carbon emissions from warm ing soils. In the Antarctic, feedback and responses to environmental change will be smaller than in the Arctic because of the less responsive cryptogams which dominate the Antarctic, the paucity of Antarctic soils, and geographical barriers to plant and invertebrate migrations.
Publisher: Royal Society
Keywords: Antarktis; biologi; botanikk; klimaendringer; lav; moser; virvelløse dyr

Solorina Spongiosa in Antarctica: An Extremely Disjunct Bipolar Lichen - Smith, R. I. Lewis; Øvstedal, Dag Olav (The Lichenologist, 1994)
The bipolar foliose lichen Solorina spongiosa (Sm.) Anzi is reported from James Ross Island, Antarctica, where it grows on moss. This is only the third known occurrence of this lichen from the Southern Hemisphere, the other localities being in Tierra del Fuego and New Zealand. Its morphology resembles that of the New Zealand population and arctic-alpine populations from the Northern Hemisphere, although there are some differences in apothecial and spore size. As elsewhere, it occupies base-rich habitats colonized by predominantly calcicolous mosses and lichens.
Edition: 2007/03/28 Publisher: Cambridge University Press
Keywords: Antarktis; botanikk; lav; moser; planter

Microclimates and water budget of algae, lichens and a moss on some nunataks in Queen Maud Land - Gjessing, Yngvar; Øvstedal, Dag Olav (International Journal of Biometeorology, 1989)
Keywords: Dronning Maud Land; NARE 1984/85; alger; biologi; lav; mikroklima; moser; planter

Bryophytes of Bouvetøya - Bell, Graham B; Blom, Hans H (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser

Lamprospora miniatopsis Spooner, a bryophilous discomycete from Bouvetøya - Schumacher, Trond (Botany of Bouvetøya, south atlantic Ocean. I. Cryptogamic taxonomy and phytogeography, 1986)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; botanikk; ekspedisjoner; moser